Python scripting for biochemistry and molecular biology in Jupyter Notebooks - Craig, Paul A.; Nash, Jessica A.; Crawford, T. Daniel (Biochemistry and molecular biology education, 2022)
A programming workshop has been developed for biochemists and molecular biologists to introduce them to the power and flexibility of solving problems with Python. The workshop is designed to move users beyond a “plug‐and‐play” approach that is based on spreadsheets and web applications in their teaching and research to writing scripts to parse large collections of data and to perform dynamic calculations. The live‐coding workshop is designed to introduce specific coding skills, as well as provide insight into the broader array of open‐access resources and libraries that are available for scientific computation.